Growth and Persistence of an Aerobic Microbial Community in Wyoming Bentonite MX-80 Despite Anoxic in situ Conditions - Burzan, Niels; Murad Lima, Roberta; Frutschi, Manon; Janowczyk, Andrew; Reddy, Bharti; Rance, Andrew; Diomidis, Nikitas; Bernier-Latmani, Rizlan (Frontiers in Microbiology, 2022)
Microbial activity has the potential to enhance the corrosion of high-level radioactive waste disposal canisters, which, in the proposed Swiss deep geological repository, will be embedded in bentonite and placed in the Opalinus Clay rock formation (OPA). Twelve stainless-steel cylindrical vessels (referred to as modules) containing bentonite were deployed in an anoxic borehole in OPA for up to 5.5 years. Carbon steel coupons were embedded in the bentonite. Individual modules were retrieved after 1, 1.5, 2.5 and 5.5 years. Enumeration of aerobic and anaerobic heterotrophs and sulfate-reducing bacteria (SRB) revealed microbial growth for 1.5 years followed by a decline or a stagnation in microbial viability. It was surprising to observe the growth of aerobic heterotrophs followed by their persistent viability in bentonite, despite the nominally anoxic conditions. In contrast, SRB numbers remained at very low levels. DNA-based amplicon sequencing confirmed the persistence of aerobes and the relatively low contribution of anaerobes to the bentonite microbiome. Bentonite dry density, in-situ exposure time, and bioavailable trapped oxygen are observed to shape the bentonite microbial community in the clay.